Oncologist‐patient‐caregiver decision‐making discussions in the context of advanced cancer in an Asian setting - Malhotra, Chetna (Health Expect, 2019)
OBJECTIVE: Patient involvement in treatment decisions is recommended in clinician‐patient encounters. Little is known about how oncologists engage patients in shared decision making in non‐Western countries. We assessed the prevalence of shared decision making among Singaporean oncologists and analysed how they discussed prognosis. METHODS: We audio‐recorded 100 consultations between advanced cancer patients and their oncologists. We developed a coding system to assess oncologist encouragement of patient participation in decision making and disclosure of an explicit prognosis. We assessed patient and oncologist characteristics that predicted these behaviours. RESULTS: Forty‐one consultations involved treatment discussions. Oncologists almost always listed more than one treatment option (90%). They also checked patient understanding (34%), discussed pros and cons (34%) and addressed uncertainty (29%). Oncologists discussed prognosis mostly qualitatively (34%) rather than explicitly (17%). They were more likely to give an explicit prognosis when patients/caregivers asked questions related to prognosis. CONCLUSION: Oncologists in our sample engaged their patients in decision making. They have areas in which they can improve to involve patients at a deeper level to ensure shared decision making. Findings will be used to develop an intervention targeting oncologists and patients to promote patient involvement in decision making.